Areal Morphometric Analysis of Adhula Drainage Basin : Using the Geospatial Techniques (International Journal of Food and Nutritional Sciences, 2022)
Basin morphometry is a means of numerically analyzing or mathematically quantifying different aspects of basin. The morphometric analysis is widely used to assess the drainage characteristics of watershed, development and management plans of the river basin. The morphometric parameters of basin can address linear, areal and relief aspects. For this study selected the Adhula basin area due to the large relief ratio as well as covering 221.94 sq. km. area. The present study deals mainly with areal morphometric parameters such as basin area, drainage density, stream frequency, texture ratio, elongation ratio, circularity ratio, form factor ratio etc. The stream frequency in the study area has shows positive correlation with the drainage density which indicates that the stream population increases with the increase of drainage density. Form factor ratio for the study area (0.1371), indicating elongated basin with flatter peak flows of longer duration. In this study using the GIS tools for the morphometric analysis. This study is very useful for planning and drainage basin management. The areal morphometric parameters are important for the integrated decision making process in flood management, soil erosion assessment and water resource management at micro level.